2014
DOI: 10.1007/s00259-014-2839-y
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment metabolic tumour volume is predictive of disease-free survival and overall survival in patients with oesophageal squamous cell carcinoma

Abstract: Metabolic tumour volume is a major prognostic factor for DFS and OS in patients with oesophageal squamous cell carcinoma. Higher SUVmax values were paradoxically associated with longer survival. The location of the tumour also appeared to affect prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
2
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 38 publications
4
25
2
3
Order By: Relevance
“…TLG and SUV max/mean did not show a significant effect. This result is in agreement with a recent publication by Lemarignier et al (8) in which MTV was prognostic for OS, whereas SUV max was not prognostic. Normalization to blood SUV and scan-time correction of SUV improved the prognostic value in our patient group, leading to comparable HRs and levels of significance for MTV and SUR values.…”
Section: Discussionsupporting
confidence: 93%
“…TLG and SUV max/mean did not show a significant effect. This result is in agreement with a recent publication by Lemarignier et al (8) in which MTV was prognostic for OS, whereas SUV max was not prognostic. Normalization to blood SUV and scan-time correction of SUV improved the prognostic value in our patient group, leading to comparable HRs and levels of significance for MTV and SUR values.…”
Section: Discussionsupporting
confidence: 93%
“…In our series, a second cancer (head and neck, lung) was subsequently diagnosed in 12 patients classified in CR when considering their oesophageal cancer. In accordance with other and our previous series [7,25,26,31,32], the initial MTV on baseline PET was significantly higher in subsequently relapsing patients than in locally controlled patients and appeared to be a major prognostic factor. Given the multiplicity of unfavourable outcomes in oesophageal cancer patients, this difference in initial volume could be helpful to select the high-risk patients in whom the investigation of alternative and more aggressive strategies would be legitimate.…”
Section: Discussionsupporting
confidence: 91%
“…The MTV was defined with a threshold at 40 % of tumour SUV max ; this value is widely used to delineate volumes with significant FDG uptake [23] and was previously used in FDG PET/CT for oesophageal cancer [24][25][26].…”
Section: Fdg Pet/ct Analysismentioning
confidence: 99%
“…MTV and total lesion glycolysis (TLG) are volume-based parameters that represent metabolic tumor burden. A number of previous studies have reported the effectiveness of MTV and/or TLG as prognostic factors in esophageal carcinoma (6,(22)(23)(24). Roedl et al (24) reported that a decrease in MTV between pre-and post-treatment PET scans was a better predictor of histopathological response, and survival in comparison with a decrease in the SUV or the clinical response evaluation based on the RECIST 1.1 in adenocarcinomas of the esophagus.…”
Section: Discussionmentioning
confidence: 99%